Diurnal Fluctuations in Acidification and Hypoxia Reduce Growth and Survival of Larval and Juvenile Bay Scallops (Argopecten irradians) and Hard Clams (Mercenaria mercenaria) - Gobler, Christopher J.; Clark, Hannah R.; Griffith, Andrew W.; Lusty, Mark W. (Frontiers in Marine Science, 2017)
Diurnal variations in pH and dissolved oxygen (DO) concentrations are common seasonal phenomena in many eutrophic estuaries, yet few studies have investigated the concurrent effects of low pH and low DO on marine organisms inhabiting these coastal systems. Here, we assess the effects of diurnal variations in pH and DO on the early-life history of two bivalve species native to Northeast US estuaries, the bay scallop (Argopecten irradians) and hard clam (Mercenaria mercenaria). In one set of experiments, larval- and juvenile-life stage bivalves were exposed to ambient conditions (pHT ~ 7.9), two continuously-low pH levels (pHT ~ 7.3 and 7.6), and diurnal fluctuations between the ambient and low conditions yielding mean pH levels equal to the intermediate pH levels. In a second set of experiments, larval bivalves were exposed to ambient conditions (pHT ~7.9, DO ~ 7 mg L-1), two levels of low pH and DO (pHT ~ 7.2, DO ~1 mg L-1; pHT ~7.4, DO ~ 4 mg L-1) and diurnal fluctuations of both pH and DO between the ambient and low pH/DO levels that resulted in mean pH and DO levels equal to the intermediate pH and DO levels. Diurnal acidification treatments with ambient DO levels yielded survival rates for both species at both life stages that were consistent with the survival of individuals exposed to the same mean level of chronic pH with juveniles being more resistant to acidification than larvae. In contrast, when both pH and DO varied diurnally, the survival rates of larval bivalves were significantly lower than the survival of individuals chronically exposed to the same mean levels of pH and DO, an indication that bivalves were physiologically more vulnerable to concurrent fluctuations of both parameters compared to acidification alone. While both species displayed sensitivities to diurnal fluctuations in pH and DO, scallops were relatively more susceptible than hard clams. Since many shallow eutrophic estuaries presently experience diurnal cycles of both pH and DO when early-life stages of bivalves are present in estuaries, the populations of the bivalves studied are likely impacted by these conditions which are likely to intensify with climate change.